Method for manufacturing transparent laminate
By forming a silicone resin layer on the resin substrate and applying mixed polysilazane, and forming a silicon dioxide-modified film with vacuum ultraviolet irradiation, the problem of insufficient weather resistance and heat resistance of the resin substrate in severe environments is solved, and efficient film thickness management and cost reduction are achieved.
Patent Information
- Application Number
- CN202280099530.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art has limitations in improving the weather resistance and heat resistance of resin substrates, especially in windshield applications in transportation equipment such as automobiles and railways, and the film thickness management cost of the modified film is relatively high.
A silicone resin layer was formed on the resin substrate, and mixed polysilazane was coated on the surface, and a silicon dioxide-modified film was formed by vacuum ultraviolet irradiation. The organic/inorganic ratio (O/P ratio) of the mixed polysilazane was adjusted to 1% by weight or more and 25% by weight or less.
By the film thickness of the mixed polysilazane layer is less than 565 nm, the weather resistance of the ultra-ultraviolet accelerated aging test (SUV) is significantly improved, the film thickness management cost is reduced, and the application scope of film thickness is expanded.
Smart Images

Figure CN119768271A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a transparent laminate for use as a windshield for vehicles such as automobiles and railways, and for transportation equipment such as airplanes and ships for seeing through or lighting purposes. Background Art
[0002] Windshields of transportation equipment such as vehicles, airplanes, and ships such as automobiles and railways are used in environments exposed to outdoor environments or under continuous friction by wipers. Resin substrates such as polycarbonate are lighter than glass substrates and are expected to replace glass substrates as window materials for perspective and lighting. The resin substrate has excellent formability, but on the other hand, the surface is very easy to be damaged. Therefore, in order to enable the resin substrate to be used in harsh environments such as windshields, a modified film with silicon dioxide as the main component is formed on the resin substrate to achieve improved scratch resistance. The modified layer is formed by coating an acrylic resin or a hard coating on the surface of the resin substrate and forming a hard film.
[0003] For example, according to Patent Document 1, a modified film mainly composed of silicon dioxide is formed by applying a silicone resin by dip coating and irradiating the surface with vacuum ultraviolet rays. This document discloses that cracks may occur when the thickness of the modified film is increased to 0.6 μm or more.
[0004] According to Patent Document 2, as a window material for a vehicle, a laminate is disclosed as follows: a hard coating layer (I) comprising a siloxane polymer component and an organic polymer component is laminated on a plastic substrate, and a silicon dioxide film (II) converted from polysilazane is further formed on the hard coating layer (I). Polysilazane is an inorganic polymer soluble in an organic solvent and having -(SiH2NH)- as a basic unit.
[0005] In the laminated body of the patent document, in the hard coating layer (I), a siloxane polymer component is relatively more present on the side in contact with the silicon dioxide film (II), and an organic polymer component is relatively more present on the substrate side. The formation of such a hard coating layer (I) is carried out by curing it by irradiating it with active energy rays after the hard coating layer is applied. The formation of the silicon dioxide film (II) is carried out by applying a coating composition containing polysilazane. By relatively more presence of a siloxane polymer component on the side in contact with the silicon dioxide film (II), the adhesion to the silicon dioxide film (II) is improved.
[0006] Patent document 3 is a technology related to a flexible barrier film used in electronic devices such as solar cells and liquid crystals. According to this technology, after applying a coating liquid containing a composition of polysilazane on an adjacent layer, a modification treatment based on vacuum ultraviolet irradiation is performed to form a barrier layer containing inorganic substances. In addition, according to this document, by providing an adjacent layer, silanol groups and the like are not generated in the polysilazane coating film before vacuum ultraviolet irradiation, and the molecular bonds of polysilazane are cut by subsequent vacuum ultraviolet irradiation to ceramicize the surface of the coating film (silicon dioxide modification). Moreover, when the film thickness of the polysilazane layer is 150nm, a film with a continuous region having a substantially constant ratio of Si, N, and O atoms of more than 2nm in the depth direction is made in an area of about 5nm to 100nm (SiO2 thermal oxidation film conversion value).
[0007] In addition, this document teaches that perhydropolysilazane is particularly preferred as the polysilazane, but also teaches the use of a mixture of perhydropolysilazane and an organic polysilazane. However, only the example of perhydropolysilazane is shown in the examples.
[0008] In the method for manufacturing a transparent laminated body of Patent Document 4, a composition containing polysilazane as a main component is applied to the surface of a silicone resin layer formed on a resin substrate, and the composition is cured to form a cured polysilazane layer converted into silicon dioxide, and vacuum ultraviolet rays with a wavelength of less than 200 nm are irradiated from above the cured polysilazane layer, so that a part of the silicone resin layer is modified into a modified film of silicon dioxide through the cured polysilazane layer. The gas volatilized by irradiating the silicone resin layer with vacuum ultraviolet rays diffuses into the resin substrate due to the gas barrier property of the cured polysilazane layer, thereby preventing the surface from being roughened and damaged, and improving the crack and peeling performance in the super ultraviolet accelerated aging test (SUV, Japanese: Super Accelerated Weathering Test).
[0009] This document teaches that perhydropolysilazane is preferred as the polysilazane, but also teaches the possibility of selecting an organic polysilazane. However, only perhydropolysilazane is shown as an example in the examples.
[0010] Moreover, perhydropolysilazane refers to polysilazane (also referred to as PHPS) in which R1, R2 and R3 of the following general formula (Chemical 1) are all hydrogen atoms. In addition, organopolysilazane refers to polysilazane (also referred to as OPSZ) in which a part of the hydrogen moiety bonded to Si of the following general formula (Chemical 1) is replaced by an alkyl group, an alkenyl group, a cycloalkyl group, an aryl group, an alkylsilyl group, an alkylamino group or an alkoxy group.
[0011] [Chemistry 1]
[0012] -Si(R1)(R2)-N(R3)-
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent No. 4536824
[0016] Patent Document 2: Japanese Patent No. 6256858
[0017] Patent Document 3: Japanese Patent No. 5935263
[0018] Patent Document 4: Japanese Patent Application Publication No. 2020-104462 Summary of the invention
[0019] Technical problem to be solved by the invention
[0020] In Patent Document 4, vacuum ultraviolet rays are allowed to reach the interface between the cured polysilazane layer and the silicone resin layer to cause an interfacial reaction, thereby penetrating the cured polysilazane layer to modify a portion of the silicone resin layer into a modified film of silicon dioxide, thereby improving the adhesion. The results show that compared with the case where the silicone resin layer not coated with polysilazane is irradiated with vacuum ultraviolet rays, the weather resistance and heat resistance are improved.
[0021] The applicant has conducted in-depth research to further improve weather resistance and heat resistance. In addition, in the document, the recommended film thickness of polysilazane is 10nm to 100nm. In such a very narrow range, it is costly to manage the film thickness quality for large areas and curved surfaces of windshields of vehicles such as automobiles and railways, aircraft, ships and other transportation equipment, so the improvement is also studied.
[0022] An object of the present invention is to provide a method for producing a transparent laminate for use as a windshield for vehicles such as automobiles and railways, and for transportation equipment such as airplanes and ships for seeing through or lighting purposes.
[0023] Means for solving technical problems
[0024] The method for manufacturing a transparent laminate of the present invention is characterized in that a silicone resin layer is formed on a resin substrate, a mixed polysilazane is coated on the surface of the silicone resin layer to form a cured mixed polysilazane layer, the mixed polysilazane is mixed at a ratio of organic polysilazane to perhydropolysilazane solid content ratio (O / P ratio) of 1wt% or more and 25wt% or less, and vacuum ultraviolet rays with a wavelength of less than 200nm are irradiated from above the mixed polysilazane layer, thereby modifying a portion of the silicone resin layer into a modified film of silicon dioxide through the mixed polysilazane layer.
[0025] Effects of the Invention
[0026] According to the present invention, it is found that the coating on the silicone resin layer becomes easier by mixing the organopolysilazane with the perhydropolysilazane, compared with the case of the organopolysilazane alone. Next, the film thickness of the mixed polysilazane layer when the coated and cured mixed polysilazane layer is irradiated with vacuum ultraviolet rays with a wavelength of less than 200nm is studied. By making the film thickness less than 565nm, a transparent laminate with excellent weather resistance for SUV can be obtained. Since the range of the film thickness of the mixed polysilazane layer can be expanded, the productivity can be improved and the quality of the film thickness can be managed for large areas and curved surfaces of windshields of vehicles such as automobiles and railways, and transportation equipment such as airplanes and ships.
[0027] Furthermore, by setting the film thickness of the polysilazane layer after ultraviolet irradiation to 100 nm to 300 nm, a transparent laminate having excellent SUV weather resistance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a diagram showing an example in which an organopolysilazane is applied onto a silicone resin layer by spin coating.
[0029] Figure 2 This is a diagram schematically showing a cross section of a transparent laminate produced by the modification method of the present invention.
[0030] Figure 3 It is a graph showing the results of weather resistance and heat resistance tests on SUVs.
[0031] Figure 4 This is a graph showing the test results of wear resistance when the O / P ratio is changed.
[0032] Figure 5 This is a graph showing the test results of the effect of the catalyst on the weather resistance of SUV.
[0033] Figure 6 This is a diagram showing the test results on the influence of increasing the irradiation amount of vacuum ultraviolet rays.
[0034] Figure 7 It is a graph showing the results of a heat resistance test, an SUV weather resistance test, and a Taber abrasion test for each film thickness. DETAILED DESCRIPTION
[0035] Perhydropolysilazane forms an inorganic film, while organopolysilazane forms an inorganic-organic hybrid film. Since the film of organopolysilazane contains an organic component, it has higher toughness than the inorganic film of perhydropolysilazane, and is expected to suppress the occurrence of cracks even when the film thickness is increased.
[0036] Therefore, the inventors used organic polysilazane, as shown in Patent Document 4, to apply a composition containing organic polysilazane as a main component on the surface of a silicone resin layer formed on a resin substrate, and cured the composition to prepare a mixed polysilazane layer converted into silicon dioxide. The inventors tried to irradiate the mixed polysilazane layer with vacuum ultraviolet rays having a wavelength of less than 200 nm from above, and evaluated the prepared samples.
[0037] Figure 1 The example of applying an organic polysilazane to a silicone resin layer by spin coating is shown. The silicone resin layer of the coating object is a hard coating layer formed by applying a siloxane resin by dip coating and curing, wherein the siloxane resin is obtained by hydrolyzing a siloxane sol obtained by a condensation reaction with an alkoxysilane as a base material. The organic polysilazane used is 1033 selected from the DURAZANE 1000 series (DURAZANE is a registered trademark of Merck KGaA). DURAZANE 1033 is a liquid, low-viscosity resin that does not require a solvent.
[0038] According to Patent Document 3, organic polysilazane has improved adhesion to the base substrate by having an alkyl group such as a methyl group, but in the applicant's test, DURAZANE 1033 bounced off into a water droplet shape and could not form a film. The test sample was DURAZANE 1033 ( Figure 1 C, 100wt%) and the proportion of DURAZANE1033 was prepared to be 25wt% ( Figure 1 A), 50wt%( Figure 1 B) sample. Thus, it is difficult to apply the organopolysilazane onto the silicone resin layer. Figure 1 D is the recognized chemical formula.
[0039] Then, the inventors found that, compared with the case of organic polysilazane alone, by mixing organic polysilazane with perhydropolysilazane, coating on the silicone resin layer becomes easier. Even when the organic / inorganic ratio (O / P ratio) of the organic polysilazane solid component and the perhydropolysilazane solid component by weight is prepared to be 3 times (the weight of the organic polysilazane solid component is 300 and the weight of the perhydropolysilazane solid component is 100), a film with a thickness of 100 nm can be formed on the above-mentioned silicone resin layer by spin coating at 3000 rpm (1 minute). The perhydropolysilazane used here is TRESMILE#100-15 of Sanwa Chemical Co., Ltd. (TRESMILE is a registered trademark of Sanwa Chemical Co., Ltd.).
[0040] Then, the study conducted a method in which a sample obtained by mixing organic polysilazane and perhydropolysilazane (hereinafter referred to as mixed polysilazane) was used, the mixed polysilazane was applied to the surface of a silicone resin layer formed on a resin substrate, the mixed polysilazane was cured to form a mixed polysilazane layer converted into silicon dioxide, vacuum ultraviolet rays with a wavelength of less than 200 nm were irradiated from above the mixed polysilazane layer, and a portion of the silicone resin layer was modified into a modified film of silicon dioxide through the mixed polysilazane layer.
[0041] In Patent Document 4, the following phenomenon is observed: when a silicone resin layer (hard coat) is formed from a polymer having a siloxane bond and irradiated with vacuum ultraviolet rays, the organic matter of the polymer volatilizes from the surface of the silicone resin layer, and the surface roughness of the modified film with silicon dioxide as the main component increases. For an initial surface roughness (Rmax) of less than 3nm, when the irradiation energy reaches 8400mJ / cm 2 When the surface roughness (Rmax) exceeds 10nm. The results of the ultraviolet accelerated aging test (SUV) based on metal halide lamps show that as the irradiation energy increases and the surface roughness increases, the time for cracking and peeling to occur becomes shorter. In order to further improve the weather resistance of SUV, reducing its surface roughness has become a countermeasure.
[0042] When a mixed polysilazane is further coated on the surface of the comparative example before irradiation with vacuum ultraviolet rays, the surface roughness will be smoothed. Moreover, even if irradiated with vacuum ultraviolet rays, the surface roughness (Rmax) is less than 3nm and hardly changes. Therefore, the inventors studied whether the weather resistance and heat resistance are improved by using a mixed polysilazane compared with the case of using perhydropolysilazane alone (patent document 4), or whether the cost of quality management of the film thickness can be reduced by being able to become a film thickness value greater than the film thickness (10 to 100nm) of the polysilazane recommended in patent document 4, even if the weather resistance and heat resistance are the same.
[0043] Figure 2 The figure schematically shows the cross section of a transparent laminate 10 produced by the modification method of the present invention, which comprises a resin substrate 1, a primer layer 2 formed thereon, a silicone resin layer 3 formed thereon, and a mixed polysilazane layer 4 formed thereon.
[0044] The resin substrate 1 is not particularly limited, and preferred raw materials include resins such as acrylic resins, polycarbonates, polyarylates, polystyrenes, polyethylene terephthalate, styrene-based polymers, and various olefin-based resins.
[0045] The primer layer 2 is provided for the purpose of improving the adhesion between the resin substrate 1 and the silicone resin layer 3, improving the impact resistance, etc., but in the present invention, it also has the effect of eliminating the scratches generated on the surface of the resin substrate 1. Such a primer layer 2 can be formed by applying various resins such as polyester resin, acrylic resin, polyurethane resin, epoxy resin, melamine resin, polyolefin resin, polyurethane acrylate resin, etc. by dip coating and curing.
[0046] The silicone resin layer 3 can be formed by applying a silicone resin by dip coating and curing, wherein the silicone resin is obtained by hydrolyzing a silicone sol obtained by a condensation reaction with an alkoxysilane as a base material. In addition, other polymers having a siloxane bond can also be used as the silicone resin layer 3. Other polymers having a siloxane bond include acrylic polymers having a siloxane bond, etc. However, when an acrylic polymer having a siloxane bond is used, the primer layer 2 is not required.
[0047] The mixed polysilazane layer 4 is obtained by mixing an organic polysilazane with a perhydropolysilazane, and in order to adjust the film thickness, viscosity, etc., the mixed polysilazane diluted with an appropriate solvent is coated on the silicone resin layer 3 by dipping, flow coating, spraying, spin coating, etc., and cured, thereby converting it into a silicon dioxide film. The curing of the mixed polysilazane can be left at room temperature for several days (in the applicant's experiment, no significant difference can be detected in the curing time (10 minutes to 3 days) and the curing temperature (room temperature to 120°C)).
[0048] Vacuum ultraviolet rays with a wavelength of 200 nm or less, such as a xenon excimer lamp (vacuum ultraviolet rays, wavelength 172 nm), are irradiated from above the mixed polysilazane layer 4. The vacuum ultraviolet rays pass through the mixed polysilazane layer 4 and modify the silicone resin layer 3 into a film with silicon dioxide as the main component from the interface between the mixed polysilazane layer 4 and the silicone resin layer 3. The modified film with silicon dioxide as the main component is composed of the film thickness of the silicon dioxide film of the mixed polysilazane layer 4 and the film thickness of the silicon dioxide film modified by the silicone resin layer 3.
[0049] (Experimental Example 1)
[0050] DURAZANE 1033 was used as the organopolysilazane, and TRESMILE #100-15 manufactured by Sanwa Chemical Co., Ltd. was used as the perhydropolysilazane.
[0051] Organopolysilazane and perhydropolysilazane were mixed to prepare 7 samples with different organic / inorganic solid content ratios (O / P weight ratio: O / P ratio): O / P ratio 1wt% (organic g / inorganic g = 1g / 100g), 5wt% (organic g / inorganic g = 5g / 100g), 10wt% (organic g / inorganic g = 10g / 100g), 25wt% (organic g / inorganic g = 25g / 100g), 50wt% (organic g / inorganic g = 50g / 100g), 75wt% (organic g / inorganic g = 75g / 100g), 90wt% (organic g / inorganic g = 90g / 100g). In addition, since TRESMILE#100-15 is diluted to 5wt% with a solvent for sale, the O / P ratio is not a ratio including the solvent, but a ratio of the solid content after removing the solvent.
[0052] Furthermore, they were diluted to 5% with dibutyl ether.
[0053] Production Figure 2 The silicone resin layer 3 shown was spin-coated at 3000 rpm for 1 minute on the surface of the silicone resin layer 3 and cured to form a mixed polysilazane layer 4 with a film thickness of 100 nm.
[0054] (Comparative Example 1)
[0055] Directly irradiate the silicone resin layer 3 with 2 J / cm 2 The upper part of the silicone resin layer 3 is modified by vacuum ultraviolet rays into a film with silicon dioxide as the main component.
[0056] (Comparative Example 2)
[0057] The silicone resin layer 3 was coated with TRESMILE#100-15 which is perhydropolysilazane and irradiated with 2 J / cm 2 The vacuum ultraviolet rays of the silicone resin layer 3 are used to modify the upper part of the silicone resin layer 3 into a film with silicon dioxide as the main component. As mentioned above, TRESMILE#100-15 is originally a chemical reagent diluted to 5 wt% by solvent. This comparative example 2 is a sample made according to the technology described in patent document 4.
[0058] The above samples were subjected to a super ultraviolet accelerated aging test (SUV weathering resistance) based on a metal halide lamp, and the time until cracking and film peeling occurred was measured. In the SUV weathering test, irradiation, darkness, and water spray were combined, and whether cracking and film peeling occurred was checked every 120 hours (the figure shows the data every 120 hours). The SUV weathering test target is 1200 hours, and the heat resistance test target is 1000 hours.
[0059] The results of SUV weather resistance and heat resistance tests are as follows: Figure 3 shown.
[0060] exist Figure 3 In A, regarding the target time of 1200 hours for SUV weather resistance, Comparative Example 1 did not reach the target time, but Comparative Example 2 did.
[0061] When the O / P ratio is 1 wt% or more and 25 wt% or less, the target time can be achieved. On the other hand, when the O / P ratio exceeds 25 wt%, the effect of the O / P ratio tends to decrease to the same degree as in Comparative Example 2 (perhydropolysilazane alone, 0 wt%). As a result, the preferred range of the O / P ratio for SUV weather resistance is 1 wt% or more and 25 wt% or less.
[0062] Figure 4 The results of the wear resistance test when the O / P ratio is changed. In the figure, the "hard coating" is an example of coating without mixed polysilazane. Among them, for the examples after the second "hard coating", the modification treatment is carried out by vacuum ultraviolet irradiation. Comparative Example 2 is the second "hard coating".
[0063] By vacuum ultraviolet irradiation, ΔHAZE≤2% was obtained, and it was found that the O / P ratio was independent of the results of the Taber abrasion test.
[0064] (Experimental Example 2)
[0065] A catalyst may be used to cure the mixed polysilazane applied on the silicone resin layer 3. When the mixed polysilazane containing a catalyst is used, the effect of the catalyst on the weather resistance of the SUV is studied. Figure 5 The results of a representative metal catalyst: palladium acetate and an amine catalyst: 4,4-trimethylenebis-(1-methylpiperidine) are shown. The mixed polysilazane used was used to form a mixed polysilazane layer 4 with an O / P ratio of 5 wt% (organic g / inorganic g=5 g / 100 g) and a film thickness of 100 nm.
[0066] From the results of palladium acetate ( Figure 5 A) and 4,4-trimethylenebis-(1-methylpiperidine) ( Figure 5 From B), no difference was found due to the type of catalyst, and it was confirmed that the weather resistance of SUV was not affected as long as the amount of catalyst was 0.5% or less. The catalyst used for curing polysilazane is as follows.
[0067] Amines:
[0068] Ammonia, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, n-propylamine, isopropylamine, di-n-propylamine, diisopropylamine, tri-n-propylamine, n-butylamine, isobutylamine, di-n-butylamine, diisobutylamine, tri-n-butylamine, n-pentylamine, di-n-pentylamine, tri-n-pentylamine, dicyclohexylamine, aniline, 2,4-lutidine, 4,4-trimethylenebis(1-methylpiperidine), 1,4-diazabicyclo[2. 2.2] Octane, N,N-dimethylpiperazine, cis-2,6-dimethylpiperazine, trans-2,5-dimethylpiperazine, 4,4-methylenebis(cyclohexylamine), stearylamine, 1,3-di-(4-piperidinyl)propane, N,N-dimethylpropanolamine, N,N-dimethylhexanolamine, N,N-dimethyloctanolamine, N,N-diethylethanolamine, 1-piperidinol, 4-piperidinol.
[0069] Organic acids:
[0070] Acetic acid, propionic acid, butyric acid, valeric acid, caproic acid
[0071] Metals:
[0072] Palladium, palladium acetate, palladium acetylacetonate, palladium propionate, nickel, nickel acetylacetonate, silver, silver acetate, silver acetylacetonate, platinum, platinum acetylacetonate, ruthenium, ruthenium acetylacetonate, ruthenium carbonyl, gold, copper, copper acetylacetonate, aluminum acetylacetonate, aluminum tris(acetoacetate)
[0073] (Experimental Example 3)
[0074] The effect of increasing the vacuum ultraviolet ray irradiation dose was studied. The experiment was conducted by forming a mixed polysilazane layer 4 having an O / P ratio of 5 wt % (organic g / inorganic g=5 g / 100 g) and a film thickness of 100 nm.
[0075] The Taber test was performed based on ASTM D1044.
[0076] In addition, the conditions in the wiper test are as follows.
[0077] Using a 400 mm long wiper, scatter sand (JIS test powder, type 1 (silica sand, particle size 45 μm to 300 μm) at a constant flow rate of 5 mm / min (7.3 g / min) to the center of the wiper range. Repeat 990 times (test time: 30 min × 33 times / min).
[0078] Figure 6 The results are shown. When the vacuum ultraviolet irradiation reaches 10J / cm 2 If the irradiation rate is above 2 J / cm, cracking or peeling will occur in the SUV weather resistance and heat resistance test. Therefore, the irradiation rate of vacuum ultraviolet rays is preferably 2 J / cm 2 Above and less than 10J / cm 2.
[0079] In Patent Document 4, when the film thickness of perhydropolysilazane alone is 88 nm, the vacuum ultraviolet irradiation dose is 2.9 J / cm 2 When the irradiation amount of vacuum ultraviolet rays is 10 J / cm2, the result of the Taber test tends to be poor. However, in Experimental Example 2 of this invention, when the polysilazane layer 4 has a film thickness of 100 nm, the result of the Taber test becomes good by increasing the irradiation amount of vacuum ultraviolet rays. 2 When the vacuum ultraviolet irradiation is 10 J / cm2, the ΔHAZE value is ≤ 1% in the Taber test and the wiper test. This is the opposite result to that in Patent Document 4. Therefore, in applications specifically for the Taber test resistance, even if the vacuum ultraviolet irradiation is 10 J / cm2, the ΔHAZE value is ≤ 1%. 2 The above also has the possibility of being used.
[0080] (Experimental Example 4)
[0081] In the above experiments, the film thickness of the mixed polysilazane layer 4 was 100 nm. Heat resistance tests, SUV weather resistance tests, and Taber abrasion tests were also conducted for other film thicknesses. The results are shown in Figure 7 . The irradiation amount of vacuum ultraviolet light is 2J / cm 2 .
[0082] For the heat resistance test, when the film thickness of the mixed polysilazane layer 4 was 565nm, the target of 1000 hours was not reached. In addition, for SUV weather resistance, when the film thickness of the mixed polysilazane layer 4 was 772nm, the target of 1200 hours was not reached. Therefore, in order to make the heat resistance and SUV weather resistance meet the targets, the film thickness is preferably less than 565nm. On the other hand, even if the film thickness of the mixed polysilazane layer 4 is 11nm, the target of 1200 hours for SUV weather resistance is achieved. Therefore, the film thickness of the mixed polysilazane layer 4 can be greater than 11nm and less than 565nm.
[0083] According to the present embodiment, it was found that by mixing the organic polysilazane with the perhydropolysilazane, the coating on the silicone resin layer 3 becomes easier than when the organic polysilazane is used alone. Next, the film thickness of the mixed polysilazane layer 4 when the coated and cured mixed polysilazane layer 4 is irradiated with vacuum ultraviolet rays with a wavelength of less than 200nm from above was studied, and it was found that if the film thickness is less than 565nm, a transparent laminate with excellent SUV weather resistance can be obtained. In Patent Document 4, if perhydropolysilazane is used alone, 100nm is the limit of the film thickness that can be thickened, but by mixing 5g of organic polysilazane in 100g of perhydropolysilazane (5wt%), the film thickness can be increased dramatically. Since the range of the film thickness of the mixed polysilazane layer can be expanded, the quality of the film thickness can be managed by improving productivity for large areas and curved surfaces of windshields of vehicles such as automobiles and railways, and transportation equipment such as airplanes and ships.
[0084] In addition, according to this example, the O / P ratio of the organopolysilazane and the perhydropolysilazane was studied, and it was found that a mixed polysilazane layer 4 having an O / P ratio of 1 wt % to 25 wt % can provide a transparent laminate having excellent SUV weather resistance.
[0085] In this embodiment, as the vacuum ultraviolet ray with a wavelength of 200nm or less, light obtained by an excimer laser or an excimer lamp with a wavelength of 157nm (F2 laser), 172nm (Xe2), or 193nm (ArF) can be used. By making the penetration depth of the vacuum ultraviolet ray into the silicone resin layer 3 greater than the thickness of the mixed polysilazane layer 4, a silicon dioxide film with a large proportion can be formed on the silicone resin layer 3 side.
[0086] Explanation of symbols
[0087] 1. Resin substrate
[0088] 2. Base coat
[0089] 3Silicone resin layer
[0090] 4. Mixed polysilazane layer
[0091] 10. Transparent laminate.
Claims
1. A method for producing a transparent laminate, characterized in that: A silicone resin layer is formed on a resin substrate. A mixed polysilazane is applied on the surface of the silicone resin layer to form a cured mixed polysilazane layer, wherein the mixed polysilazane is mixed at a ratio of 1 wt % to 25 wt % of solid content (O / P ratio) of organic polysilazane to perhydropolysilazane, By irradiating the mixed polysilazane layer with vacuum ultraviolet light having a wavelength of 200 nm or less from above, a part of the silicone resin layer is modified into a modified film of silicon dioxide through the mixed polysilazane layer.
2. The method for producing a transparent laminate according to claim 1, wherein: The thickness of the mixed polysilazane layer is set to be not less than 11 nm and less than 565 nm.
3. The method for producing a transparent laminate according to claim 1, wherein: The irradiation amount of the vacuum ultraviolet light is 2J / cm 2 Above and 8J / cm 2 the following.
Citation Information
Patent Citations
Memory control circuit
JP1984035263A
Flaw passage changing device
JP1987056858A
Method for manufacturing gas barrier film
CN105593013A
Barrier film, method of forming the same and organic photoelectric transducer
JP2011068042A
Method for producing gas-barrier film and organic electronic device
JP2012000546A